2020
DOI: 10.1038/s41598-020-66303-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Human Autonomic Neurons Enables Precise Control of Cardiomyocyte Beating

Abstract: The autonomic nervous system (ANS) regulates tissue homeostasis and remodelling through antagonistic effects of noradrenergic sympathetic and cholinergic parasympathetic signalling. Despite numerous reports on the induction of sympathetic neurons from human pluripotent stem cells (hPSCs), no induction methods have effectively derived cholinergic parasympathetic neurons from hPSCs. Considering the antagonistic effects of noradrenergic and cholinergic inputs on target organs, both sympathetic and parasympathetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…3D projections of cocultures confirmed that axons and the clustered synaptic protein SynI were located very close to CMs, indicating that neurons and CMs can interact via axon-mediated synaptic connections. In previous neuron–CM coculture studies, the presence of synaptic proteins near CMs has not been evaluated except for by Takayama et al [ 13 ], although later, they showed that hiPSC-neurons expressed synaptic proteins in free cocultures with CMs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3D projections of cocultures confirmed that axons and the clustered synaptic protein SynI were located very close to CMs, indicating that neurons and CMs can interact via axon-mediated synaptic connections. In previous neuron–CM coculture studies, the presence of synaptic proteins near CMs has not been evaluated except for by Takayama et al [ 13 ], although later, they showed that hiPSC-neurons expressed synaptic proteins in free cocultures with CMs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the functionality of neuron–CM interactions has been reported in models utilizing rat primary neurons and CMs [ 10 , 11 ] and rat primary neurons and hiPSC-CMs [ 12 ] with integrated MEAs. Furthermore, MEAs have been utilized in cardiac innervation models where CMs have been seeded on top of neurons [ 15 , 35 ]. In these studies, neuronal stimulation evoked a response in the CMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancement of neuron-specific mouse models; viral gene transfer; and new technologies, including optogenetic and chemogenomic stimulation, has allowed for more specific study within these pathways [140]. Another limitation to studying the role of Ang II in parasympathetic neurotransmission is the lack of reliable and reproducible 'parasympathetic' cell lines, although recent progress may change this in the future [141]. A stepwise neurotropic chemical induction method of human pluripotent stem cells developed by Takayma et al can be used to induce both sympathetic-like and parasympathetic-like autonomic nervous system neurons [141].…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…Another limitation to studying the role of Ang II in parasympathetic neurotransmission is the lack of reliable and reproducible 'parasympathetic' cell lines, although recent progress may change this in the future [141]. A stepwise neurotropic chemical induction method of human pluripotent stem cells developed by Takayma et al can be used to induce both sympathetic-like and parasympathetic-like autonomic nervous system neurons [141]. Work has been published on modifying this technique to study sympathetic neurons; however, its use for differentiation of parasympathetic cells is still untested [142].…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%